Isolation, screening antimicrobial activity and identification of fungi from marine sediments of the area Thanh Lan, Co To, Vietnam - Hong Minh, Le Thi; Mai Anh, Nguyen; Thi Quyen, Vu; Thu Huyen, Vu Thi; Mai Huong, Doan Thi; Van Cuong, Pham; Van Minh, Chau (Vietnam Journal of Biotechnology, 2020)
Marine environment is rich in natural product resources, including marine microorganisms, especially fungi which are not only seen as a potential source of highly applicable bioactive substances but also can provide for science new chemical structures. The objective of this study is to isolate and screen fungal strains with antibacterial activity from the marine environment. Twenty five strains of fungi were isolated from marine sediments of Thanh Lan, Co To island and assessed on antibiotic activity against 7 tested microbial strains, including three Gram-negative bacteria (Escherichia coli ATCC25922, Pseudomonas aeruginosa ATCC27853, Salmonella enterica ATCC13076), three Gram-positive bacteria (Enterococcus faecalis ATCC29212, Stapphylococus aureus ATCC25923, Bacillus cereus ATCC 13245), and the yeast Candida albicans ATCC10231. The minimum inhibitory concentration (MIC) against the tested microorganisms was determined for the crude extracts obtained from the culture broths after ethyl acetate extraction and vacuum rotary evaporation. Three strains with the highest antimicrobial activity M26, M30 and M45 were capable of inhibiting 4 - 5 of the 7 tested microorganisms with MIC values from 64 to 256 μg/ml, depending on each tested strain. Morphological and phylogenetic investigations based on 18S rRNA gene sequences of the three selected strains showed that strains M26 and M30 belonged to the genus Penicillium, whereas strain M45 belonged to the genus Neurospora. The sequences of 18S rRNA gene of three strains M26, M30 and M45 were registered on GenBank database with accession numbers: MH673730, MH673731, MH673732, respectively. Research results showed that marine environment has a great potential in isolation of fungal strains for the search for antibacterial substances as well as other biologically active compounds.